کۆنتڕۆڵی کۆمەڵایەتی و پەیوەندی بە ڕەفتاری سەربەخۆی منداڵانەوە لەڕوانگەی مامۆستایانی باخچەوە لە شاری سلێمانیدا - خالد, حسن فخرالدين; عبدالرحمن, ئاڤان عمر (Sulaimani Journal for Humanities, 2022)
The aim of this research is to investigate social control and its relationship with the children's independent behavior from the perspective of kindergarten teachers، as well as to investigate the level of social control for kindergarten teachers، and children's independent behavior from the teachers' point of view according to the variables gender، education، kindergarten type، years of service، and certified level of acquired education. In addition، the researcher has used the method of description to achieve these goals، because it is compatible with the objectives and nature of the research. The research tool consists of a questionnaire for each of the social control variables، which comprises 48 sections divided into the following two fields: punishment and remuneration created by the researcher، and independent behavior variable consisting of 30 sections. The researcher had prepared the scale by using previous resources and previous research subsequent to ensuring the validity and reliability of the instruments. The data collection method was executed on to the sample of research، which consists of 250 kindergarten teachers in Sulaymaniyah. In order to analyze and interpret the results of the collected data، the researcher used the "SPSS" statistical program to treat statistics and analyze data and information. Finally، the following results can be concluded based on the research: 1-The level of social control of kindergarten teachers is generally high. 2-There are no statistically significant differences in the level of social control among kindergarten teachers according to the gender variable (males and females). 3-There are no statistically significant differences in the level of social control among kindergarten teachers according to the variable years of service. 4-The level of children's independent behavior from the point of view of kindergarten teachers in the city of Sulaymaniyah is generally high. 5-There are no statistically significant differences in the level of children's independent behavior from the point of view of kindergarten teachers according to the gender variable (male and female). 6-There are no statistically significant differences in the level of children's independent behavior from the point of view of kindergarten teachers according to the variable years of service. 7- There is a positive relationship between social control and children's independent behavior from the point of view of kindergarten teachers in Sulaymaniyah.